1998
DOI: 10.1302/0301-620x.80b4.8216
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of hip dislocation in children with arthrogryposis multiplex congenita

Abstract: Arthrogryposis multiplex congenita (AMC) is a rare disease with multiple joint contractures. It is widely believed that bilaterally dislocated hips should not be reduced since movement is satisfactory and open reduction has had poor results. Since 1977 we have performed a new method of open reduction using an extensive anterolateral approach on ten hips in five children with AMC. The mean age at surgery was 31.5 months (17 to 64) and the mean follow-up was 11.8 years (3.8 to 19.5). At the final follow-up all c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
10

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 5 publications
3
42
0
10
Order By: Relevance
“…Historically, emphasis was placed on treating unilateral dislocation aggressively due to risk of developing scoliosis and pelvic obliquity while bilateral dislocations could be treated conservatively 4. Recently, there has been a trend towards surgical management of all dislocations in these patients 9 10…”
Section: Discussionmentioning
confidence: 99%
“…Historically, emphasis was placed on treating unilateral dislocation aggressively due to risk of developing scoliosis and pelvic obliquity while bilateral dislocations could be treated conservatively 4. Recently, there has been a trend towards surgical management of all dislocations in these patients 9 10…”
Section: Discussionmentioning
confidence: 99%
“…Seventy-seven surgical procedures were performed overall; the mean number per child was 7 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Bilateral surgery was considered as two procedures, even if they were done during the same anaesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…The rate of complication led most authors to recommend that bilateral dislocation left unreduced [2,10,11,18]. Nevertheless, several authors published good results for most of their bilateral open reductions with a follow-up before skeletal maturity (between 65 months and 11.8 years) [12][13][14]19]. In 2002, Yau et al showed in their study a correlation between the final radiographic status and the St. Clair functional hip score.…”
Section: Treatmentmentioning
confidence: 99%
“…Lorsqu'il existe une luxation de la hanche, le membre se place en flexion-adduction. L'atteinte de la hanche, avec ou sans luxation, a été rapportée chez environ 80 % des patients atteints d'arthrogrypose [9]. L'épaule est souvent fixée en adduction et en rotation interne avec mobilité réduite.…”
Section: Discussionunclassified
“…Au niveau des membres inférieurs, les indications chirurgicales sont en revanche plus fréquentes. La luxation de la hanche nécessite le plus souvent une réduction chirurgicale chez les enfants marchant, avec un risque de complications comme la reluxation, la raideur ou la nécrose avasculaire [9,23]. Un flessum de hanche de plus de 458 peut être traité par ostéotomie fémorale de déflexion.…”
Section: Discussionunclassified